A Natural Flavonoid Glucoside, Icariin, Regulates Th17 and Alleviates Rheumatoid Arthritis in a Murine Model. (12th October 2014) - Chi, Liqun; Gao, Wenyuan; Shu, Xiangrong; Lu, Xin
Abstract : Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease that causes deformity of the joints and physical disability. Icariin, a natural flavonoid glucoside isolated from plants in the Epimedium family, has been proven to have various pharmacological activities. A recent study showed that icariin suppressed cartilage and bone degradation in mice of collagen-induced arthritis. However, the mechanism needs to be further investigated. In our current study, we found that icariin reduced the arthritis score and the incidence of arthritis compared with that in mice treated with water. Icariin inhibits the expression of various osteoclastogenic markers, such as β 3 integrin, cathepsin K, and MMP9 in vitro . Icariin treatment in mice with CIA also resulted in less number of Th17 cells and decreased ratio of CD4 + IL-17 + cells. The alleviated arthritis score and incidence of arthritis and reduced serum levels of IgG2a induced by icariin were abolished with additional IL-17 administration. Furthermore, icariin inhibited STAT3 activation in T cells and STAT3 inhibitor resulted in decreased IL-17 production and alleviated RA. In conclusion, icariin decreases Th17 cells and suppresses the production of IL-17, which contributes to the alleviated rheumatoid arthritis, through the inhibition of STAT3 activation.